Logic and argumentation - Monsalve, Alfonso (Estudios de Filosofía, 1990)
In its first part, this paper offers a summary of Chaim Perelman and Lucie Olbrechts-Tyteca’s theory of argumentation. The essential elements of this theory are stressed: its point of departure as a critique of the classical Western conception of rationality, assumed, since Descartes, as being identical with demonstrative reason; the Aristotelic origin of argumentation in the Rhetoric or Art of Persuasion; the concept of a "universal auditorium", as addressee of the arguments; the notion of what is "reasonable" and its relation to the concept of what is "rational". The second part submits the authors’ position regarding the relationsbip between what is rational and what is reasonable to criticism. A thesis is supported according to which what is rational is the necessary condition of what is reasonable (a position that is not accepted by Perelman and Olbrechts); to achieve this, it is appealed to Piaget’s ideas on the existence of a "natural logic"; the concept of Calculus of natural deduction is employed as a type of logical formalism applied to argumentation; Apostel and Grice’s ideas concerning conversational implication are used and the formalism developed by von Wright for the logical analysis of action is applied, in order to classify the elementary types of argumentative action.